Spatial distribution of waste collection points and their implications on quality of life in Mombasa County, Kenya - Ezra Wekisa; Christine Majale (Journal of Urban Management, 2020)
Quality of life index is a measure used to describe the living environment experienced by a segment of the population. Correspondingly, waste collection and transfer are the core of waste management chain and is influenced by the four capitals of sustainability - economic capital, physical capital, environmental capital and social capital. Mombasa generates approximately 2200 tons of waste and only 65% are collected and 13% of households' access county (local authority) waste management services due to mismanaged primary collection points. In ascertaining the link between primary collection points and quality of life, indicators used to construct the index were defined and weighting assigned based on their impact on the environment. This study employed both descriptive study approach and mixed methods involving quantitative and qualitative methods to collect and infer the data. The study showed that Mombasa County is served by nine designated collection points that are inadequate and has led to the emergence of informal collection points and exposed the residents to communicable diseases. The attitude of the residents on waste management is wanting and has exacerbated the waste management drive in the county. Correspondingly 74% of the respondents used in the study have reservations regarding the waste management conduct and practices as currently practised by the local authority. Quality of life index was arrived at with more emphasis and higher weighting on the environmental aspect. The aggregated quality of life index highlighted areas with more concentration of collection points enjoy low quality of life and converse.
Keywords: 710; Indicators; Primary collection points; Quality of life; Waste collection